Leveraging Telehealth: Utilizing Digital Health Technology to Improve Patient Care in Orthopaedics. Issue 5 (11th May 2022) - Maheu, Arlene R.; Atanda, Alfred
Abstract : The past decade has seen a shift in health care delivery models to be more value-based: patient-centered, accessible, and cost-effective. One of the primary modes of addressing these needs has been through the implementation of telemedicine—digital health care technology that streamlines and enhances traditional health care delivery. In the orthopaedic setting, there are various methods of telemedicine utilization, each uniquely optimized for different clinical scenarios. There are certain financial and technological limitations when utilizing telemedicine for orthopaedic care that pose notable barriers to uniform utilization across the specialty. Nonetheless, these challenges are currently being tested as orthopaedic surgeons continuously become more innovative and creative as to how they deliver care. As we enter our "new normal" in the post-COVID-19 era, the availability and use of telemedicine will equip orthopaedic surgeons to deliver high-quality, affordable, and accessible care in an ever-changing health care landscape.